Negotiating Sexuality Education with Young People: Ethical Pitfalls and Provocations. Issue 2 (3rd April 2019) - Ollis, Debbie; Coll, Leanne; Harrison, Lyn
Abstract: This paper focuses on a nested project within a three-year participatory research project, funded by the Australian Research Council. The project was undertaken in secondary schools across Victoria and South Australia and engaged over 100 students as coresearchers (ages 15–19) in understanding, critiquing, and transforming sexuality education (SE). Data was produced through visual arts and participatory methods and supported by ethnographic techniques (participant observations, focus groups, and guided conversations). In this paper we attempt to expose some of the ethical, methodological and pedagogical processes required when foregrounding young people's voices in SE. More specifically, to problematize the microethical moments that warrant not only the attention but response of educators and researchers who are open to transforming SE with young people.